Kepuasan Pelanggan terhadap Kualiti Perkhidmatan Perpustakaan Universiti Malaysia Sarawak - Shellya, Binti Zainal Barahim (Universiti Malaysia Sarawak (UNIMAS), 2012)
Quality is a continuous process from time to time to ensure that the relationship between an organization and its customers are always sustained the process of improvement of the quality of the ongoing quality of service to ensure customers achieve maximum satisfaction when using the services provided. Customer satisfaction depends on the quality of services provided by the organizations they serve. Provisions of good quality services or otherwise, influence the level of customer satisfaction. The purpose of this study was to determine the students' level of satisfaction on the quality of services provided by the Library of UNIMAS. Based on the test mean score for the threedimensional services mean score for frontline services and core service is good. Based on the results of the correlation test showed the three service dimensions have a significant relationship with customer satisfaction. Regression analysis showed that the factors most affect the performance of front-line service dimension is an online public catalog. While the factors affecting the performance of basic services are the dimensions of the library staff and ancillary services are customer convenience factor. In conclusion, customers are satisfied with the quality of services provided by the Library UNIMAS although there are some weaknesses.